Dogmatism On the History of a Scholarly Vice - Paul, Herman (Bloomsbury Academic, 2024)
Why does the history of dogmatism deserve our attention? This open access book analyses uses of the term, following dogmatism from Victorian Britain to Cold War America, examining why it came to be regarded as a vice, and how understandings of its meaning have evolved. Whilst the field of scientific thought is committed to continuous innovation, ideas about dogmatism - with their roots in ancient philosophy - are pervasive in scientific thought today. Carrying connotations of both vice and ecclesiastical authority, the term's prevalence during the 'age of science', and the rise of new thought categories such as totalitarianism and creationism, prompted scholars to repeat the old wisdom that science is incompatible with dogmatism. Tracing the concept across decades and different disciplines, Paul and Stoeger demonstrate how it has survived not only the passage of time, but changes in language and scientific methodologies. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Dutch Research Council (NWO).